Handbook of Second Language Acquisition 1996
DOI: 10.1016/b978-012589042-7/50005-0
|View full text |Cite
|
Sign up to set email alerts
|

Universal Grammar and Second Language Acquisition

Abstract: Constraints on representationIn this paper, I provide an overview of differing perspectives on the role of Universal Grammar (UG) in second language acquisition (SLA). I will suggest that we must not lose sight of the fact that UG is a theory which provides constraints on linguistic representation. At issue, then, is whether interlanguage (IL) representation is constrained by UG.UG is part of an innate biologically endowed language faculty. It places limitations on grammars, constraining their form (the invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 40 publications
0
23
0
2
Order By: Relevance
“…Using a GJT and a Written Elicited Production Task to tap the learners' knowledge of grammatical wh-question formation in English, the researchers found that almost all the high-intermediate group and half of the low-intermediate group perform like the native English speaking control group; hence, the L1 is not the only source of the learners' UG-like knowledge. Rather, principles of UG remain accessible in adult L2 acquisition, and can be triggered properly by increasing the level of general proficiency (White, 1996).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Using a GJT and a Written Elicited Production Task to tap the learners' knowledge of grammatical wh-question formation in English, the researchers found that almost all the high-intermediate group and half of the low-intermediate group perform like the native English speaking control group; hence, the L1 is not the only source of the learners' UG-like knowledge. Rather, principles of UG remain accessible in adult L2 acquisition, and can be triggered properly by increasing the level of general proficiency (White, 1996).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Ellis 1985;Klein 1986;Klein and Perdue 1993;Kowal and Swain 1997;Selinker and Lamendella 1978; Wong-Fillmore 2002) • age (passim the SLA literature) • lack of written input (e.g. Schmidt 1983;VanPatten 1988) • false automatization (Hulstijn 1989(Hulstijn , 2002a • end of sensitivity to language data (Schnitzer 1993) • lack of access to UG learning principles (White 1996) • learning inhibits learning 5 (Elman et al 1996) • language transfer (e.g. Han 2000;Jain 1974;Kellerman 1989;Major 2002;Selinker and Lakshmanan 1992).…”
Section: Putative Causal Variablesmentioning
confidence: 99%
“…This obtained result has, however, contradicted Bley-Vroman's belief that states that access to UG is only via the L1. Moreover, it has opposed the belief of those researchers who claim no access to UG at all such as Clahsen and Muysken (1986) (White, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%